Congenital brucellosis associated with subsequent Klebsiella pneumoniae co-infection in a premature neonate: A rare case report - Jaber Al-Faifi; Mutasim E. Ibrahim (Elsevier, 2022)
We report a case of congenital brucellosis subsequently associated with Klebsiella pneumoniae infection in a Saudi preterm neonate. A girl born with severe respiratory distress was admitted to a neonatal intensive care unit. Laboratory examinations revealed thrombocytopenia and slight leukocytosis. Her mother was a confirmed case of brucellosis. Initial blood culture confirmed the diagnosis of infection, and the baby was treated empirically with rifampicin, gentamicin, and ciprofloxacin. Follow-up revealed that her general condition was gradually improved. On day 27, the baby deteriorated, showing abdominal distension and signs of sepsis and requiring intubation. Rifampicin was replaced by amikacin. A septic workup showed a normal total leukocyte count, with 68.3% neutrophils, decreased platelet count, and increased C-reactive protein level. Blood culture and sensitivity testing reported multidrug-resistant K. pneumoniae susceptible to amikacin and resistance to gentamicin, ciprofloxacin, and beta-lactam antibiotics. The baby remains critically ill, showing a poor treatment response with rapid deterioration, and arrested on day 33. Concomitant bacterial infections might explain signs of sepsis and respiratory distress among neonates with congenital brucellosis. Accurate and early diagnosis, parental history, and adequate treatment are associated with the prognosis of congenital brucellosis and other related bacterial infections.